Assessment of Flood Risk Analysis in Selangor - Md Lazam, Norazliani; Nazatul Shima Syed Mohamed Shahruddin, Sharifah; Haris Baharrudin, Muhammad; Md Jani, Hanisah; Farahin Azhari, Azyan; Farisya Farhani Khairul Nizam, Nur (International Journal of Engineering and Technology, 2019)
Flood events occur every year especially during the monsoon season. Although its consequences are not as disastrous as other natural disasters such as earthquakes and tornado storm, but it still gives off a great deal of destruction towards social, operational and financial sectors. Recently, most of the events occurred are not happened at the common marked areas and seasons. It happened anywhere and anytime. Hence, it is not surprise that at any time, any place could be affected by flood incidents. Therefore, an analysis on flood incident is crucial in mitigating the flood risk and at the same developing the flood safety measures. This study aims to analyse the flood frequency and flood magnitude of all nine districts in Selangor. Data is gathered from the Department of Irrigation and Drainage (DID) Selangor, from 2008 to 2017. Petaling Jaya posted the highest number of flood cases at 249 cases out of 1,161 cases in Selangor throughout the period of 2008 to 2017. Poisson distribution was used to estimate the probability of flood occurrence, and the results show that Petaling Jaya has recorded the highest probability of flood occurrence with at least one event in a day. For severity analysis, Gumbel distribution was used to estimate the magnitude of flood occurrence and flood frequency through the evaluation of flood risk from the annual maximum number of rainfall data. Results indicate that Sabak Bernam recorded the biggest magnitude of severity with moderate flood as compared to other districts. It is also estimated that Sabak Bernam has the biggest magnitude of flood recurring as early as two years return period. To conclude, authorities must work vigorously towards an efficient flood risk management and effective flood safety measures. The establishments of flood forecasting and warning system are crucial in minimising the flood losses. Â